A study of the sintering behaviour of magnesium diboride - Dancer, C; Mikheenko, P; Bevan, A; Abell, J; Todd, R; Grovenor, C (2009)
It is well known that a substantial increase in critical current density can be achieved by the heat-treatment of ex situ magnesium diboride powder-in-tube wires. However, it is not clear whether this is due to a true sintering process involving the significant transport of material and densification, or due for instance to the removal of volatile impurities from particle interfaces, limited chemical reactions at particle boundaries, or simply contact formation between particles by thermally activated direct adhesion. We believe that the term sintering in the magnesium diboride literature may often be used loosely when neither neck formation nor densification occurs during heat-treatment, and have designed experiments to understand what is happening during this processing step. We have studied the effect of a range of heat-treatments on the microstructure of pellets produced from commercial MgB2 powder using X-ray diffraction, scanning electron microscopy, Vickers hardness tests and by density measurements using Archimedes' principle. The results are compared to those from a dense sample produced from the same powder by resistive sintering. No significant densification is observed in pellets produced by conventional pressure-less heat-treatment up to 1100 °C. However, a clear correlation between density and hardness is established by comparison with results for bulk MgB2 produced by resistive sintering, which confirms that a classical sintering process has been induced in the latter samples. © 2008 Elsevier Ltd. All rights reserved.